2022
DOI: 10.3389/fneur.2022.948462
|View full text |Cite
|
Sign up to set email alerts
|

VOR gain of lateral semicircular canal using video head impulse test in acute unilateral vestibular hypofunction: A systematic review

Abstract: IntroductionAcute unilateral vestibular hypofunction is characterized by sudden onset of vertigo or dizziness, vomiting/nausea, gait instability, and nystagmus. This is commonly described as an acute vestibular syndrome and usually attributed to vestibular neuritis; however, up to 25% of acute vestibular syndrome is caused by a stroke of posterior circulations. The video head impulse test is a recent tool in the vestibular test battery that assesses the vestibule-ocular reflex by measuring the VOR gain and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…VOR gain was calculated with OTOsuite software (GN Otometrics, Taastrup, Denmark). Abnormal results were defined as a lateral canal VOR gain less than 0.7, based upon previously established clinical cutoffs ( Alfarghal et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…VOR gain was calculated with OTOsuite software (GN Otometrics, Taastrup, Denmark). Abnormal results were defined as a lateral canal VOR gain less than 0.7, based upon previously established clinical cutoffs ( Alfarghal et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…This test collects computerized vestibulo-ocular reflex, measuring the speed of head movement and the ocular response. Two parameters will be measured: the gain (ratio between cephalic and ocular movement, which should be close to 1 and is pathological if it is less than 0.8) and the occurrence of saccades (late responses produced by the central neuronal system indicating pathology) [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Participants in the EX group will train for two non-consecutive days per week for eight weeks under the supervision of exercise specialists (sports physical educators). All sessions will start and finish with BP measurements, and participants’ physical effort will be monitored by HR monitors (Polar Electro, Kempele, Finland) and the rate of perceived exertion using the original Borg scale [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ]. Each session ( Appendix A ) will include a standardized 15-min warm-up with joint mobility exercises and gait technique and a 5-min cooldown with basic stretching exercises and controlled breathing.…”
Section: Methodsmentioning
confidence: 99%
“…VRT is another treatment option that can be effective in improving balance and reducing dizziness in patients with BPPV and with affected quality of life [ 33 , 34 ]. VRT involves a series of exercises designed to promote central nervous system compensation for inner ear deficits and improve overall vestibular function [ 33 , 34 ].…”
Section: Reviewmentioning
confidence: 99%
“…VRT is another treatment option that can be effective in improving balance and reducing dizziness in patients with BPPV and with affected quality of life [ 33 , 34 ]. VRT involves a series of exercises designed to promote central nervous system compensation for inner ear deficits and improve overall vestibular function [ 33 , 34 ]. Studies have shown that VRT can lead to significant improvements in symptoms, which include unsteadiness and fear of falling, which can affect the quality of life for patients with BPPV [ 33 , 34 ].…”
Section: Reviewmentioning
confidence: 99%